POLA PIKIR (MINDSET) GURU DALAM MENERAPKAN PENDEKATAN SAINTIFIK PADA PEMBELAJARAN MATEMATIKA DITINJAU DARI GENDER - Juwariah, Nunung; Kusmayadi, Tri Atmojo; Usodo, Budi (Jurnal Pembelajaran Matematika, 2015)
Abstract: The aims of this research were to describe the mindset of female and male teachers in implementing the scientific approach to the study of mathematics. It was a qualitative research. The subjects were taken by purposive sampling. The subjects of this research were mathmatics teachers of class X SMAN 3 Madiun. The subject of the research as much as 2 teachers consisted of 1 male teacher and 1 female teacher.Data collection techniques in this research wereÂ  interviews and observation. Techniques to validate the data source triangulation and time triangulation. The data analysis technique used was the concept of Miles and Huberman consisted of data reduction, data display, and conclusion. The research findings are as follows (1) the female teacher do not always apply a scientific approach. During observation process, female teacher used abstract mathematic object. During question activity female teacher had obstacles. To solve this obstacle, female teacher usually persuades students with statements. During experiment activity, female teacher created guidance question. During mobilization activity, female teacher provide questions that provoke and leads to mathematics concepts. During communication activity, female teacher using presentation although it require long time. (2) during observation male teacher used approach from learned students. during question activity, the male teacher of dividing students became some group then provide opportunitie for students to ask on a friend in the group. During mobilization activity, teacher must have perfected mathematical concepts which belongs to the students. During communication activity, male teacher asked the students to present the result of that has accured. Keywords: Mindset, scientific approach, gender.